(untitled) (International Journal of Engineering and Computer Science, 2014)
The cutting edge of technology is data mining. We apply data mining techniques in various fields and the results are enormous. Assessment is important to check your quality, and these metrics or measures play a vital role in guiding the work. This paper summarizes various evaluation measures criteria for assessment of data mining tasks. In this paper data mining functionalities (classification, clustering, Association rule mining) assessment metrics are discussed.